Treatment of Infantile Hemangioma - Indri Widya Sari; Fitriani Fitriani; Soenarto Kartowigno (HM Publisher, 2021)
Infantile hemangioma represents the most common benign tumour arising ininfancy. The natural history of infantile hemangioma is characterized by aproliferative phase during the first few months of life, followed by slower involutionover the years. Evolution of infantile hemangioma has four stages, contain nascent,proliferation, involution, and involuted. Most infantile hemangioma do not requireactive treatment and involute without leaving significant residual. However, someinfantile hemangioma is problematic due to complications such as ulceration,interference with a vital function, or potential disfigurement. The managementapproach for IH contains active non-intervention and active intervention. Thedecision of treatment is based on many factors, including size and location,psychosocial implication, risks and benefits of the proposed therapy. Earlyrecognition of infantile hemangioma is essential for optimal management andpreventing complication.